2015
DOI: 10.1371/journal.pone.0134539
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Lamivudine-Resistant HBV during Antiretroviral Therapy Including Lamivudine for Patients Coinfected with HIV and HBV in China

Abstract: In China, HIV-1-infected patients typically receive antiretroviral therapy (ART) that includes lamivudine (3TC) as a reverse-transcriptase inhibitor (RTI) (ART-3TC). Previous studies from certain developed countries have shown that, in ART-3TC, 3TC-resistant HBV progressively emerges at an annual rate of 15–20% in patients coinfected with HIV-1 and HBV. This scenario in China warrants investigation because >10% of all HIV-infected patients in China are HBV carriers. We measured the occurrence of 3TC-resistant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 28 publications
(36 reference statements)
4
17
1
Order By: Relevance
“…We identified a patient with phenotypic evidence of 3TC-resistant HBV in our cohort, congruent with evidence for the consistent selection of resistance among individuals on 3TC monotherapy [42], and in keeping with another African study that documented a high prevalence of 3TC resistance among coinfected patients [4]. Tenofovir resistance is less well substantiated, and can be difficult to confirm phenotypically due to the slow rate of HBV DNA suppression after institution of therapy [26]; however, there are reports confirming the potential for resistance to this agent (as previously reviewed [8,34]).…”
Section: Drug Resistancesupporting
confidence: 77%
“…We identified a patient with phenotypic evidence of 3TC-resistant HBV in our cohort, congruent with evidence for the consistent selection of resistance among individuals on 3TC monotherapy [42], and in keeping with another African study that documented a high prevalence of 3TC resistance among coinfected patients [4]. Tenofovir resistance is less well substantiated, and can be difficult to confirm phenotypically due to the slow rate of HBV DNA suppression after institution of therapy [26]; however, there are reports confirming the potential for resistance to this agent (as previously reviewed [8,34]).…”
Section: Drug Resistancesupporting
confidence: 77%
“…It is known that the HBV viral load is related to the presence of HBeAg, [4] and lamivudine alone is less effective in reducing the HBV viral load. [26,27] We also found that a higher level of education was associated with active HBV replication. This may be because patients with a lower level of education tend to acquire HBV infection earlier during childhood, through horizontal transmission among toddlers, and have therefore lost HBeAg, whereas patients with a higher level of education tend to acquire HBV later in life through sexual exposure.…”
Section: Active Hbv Replication In Hbsag-positive Patientsmentioning
confidence: 61%
“…This is compared to other HIV/HBV co-infection studies, which did not stratify by baseline HBV DNA, that have shown approximately 30-60% achieving HBV DNA suppression with 3TC monotherapy at 48 weeks 19-21 . A recent study from China with a small number of HIV/HBV co-infected subjects demonstrated that 3TC monotherapy was associated with higher rates of 3TC-resistant HBV compared to TDF+3TC 22 , but in this study, the authors did not stratify their analyses with baseline HBV DNA levels. Our multivariable analysis demonstrates that TDF is associated with HBV DNA suppression when HBV DNA ≥ 20,000 IU/ml (Table 2) or when HBeAg is negative (Supplementary Table S2) at baseline.…”
Section: Discussionmentioning
confidence: 93%